Understanding the Impact and Tackling the Burden of Osteoarthritis for Aboriginal and Torres Strait Islander People. Issue 1 (10th October 2022) - O'Brien, Penny; Prehn, Ryan; Green, Charmaine; Lin, Ivan; Flanagan, Wanda; Conley, Brooke; Bessarab, Dawn; Coffin, Juli; Choong, Peter F. M.; Dowsey, Michelle M.; Bunzli, Samantha
Abstract : Objective: The aim of this study was to understand and describe the lived experience of Aboriginal and Torres Strait Islander people with osteoarthritis. Methods: Qualitative study guided by cultural security, which ensures that research is conducted in a way that will not compromise the cultural values, beliefs, and expectations of Aboriginal and Torres Strait Islander people. Participants were purposively sampled through the networks of project staff. Research yarns (a cultural form of conversation used as a data gathering tool) were conducted with 25 Aboriginal and Torres Strait Islander adults with self‐reported osteoarthritis in Western Australia and Victoria, Australia. Data were analyzed using a framework approach and presented through composite storytelling (hypothetical stories representing an amalgam of participants' experiences). Results: Two composite stories were constructed to reflect themes relating to beliefs and knowledge, impact, coping, and health care experiences. Common beliefs held by participants were that osteoarthritis is caused by previous physically active lifestyles. Many participants feared for their future, increasing disability and needing a wheelchair. Pain associated with osteoarthritis impacted daily activities, sleep, work, family, and social life and cultural activities. Multidimensional impacts were often experienced within complex health or life circumstances and associated with increased anxiety and depression. Most participants reported negative health care experiences, characterized by poor patient–provider communication. Conclusion: Our findings highlight that osteoarthritis is a multidimensional issue for Aboriginal and Torres Strait Islander people that permeates all aspects of life and highlights the need for integrated, multidisciplinary care that is culturally informed and individualized to patient need.